A Qualitative Study of Therapist Trainees’ Multicultural Counselling Development Through Working With Refugee Clients: Implications for Theory-Building, Research, and Practice - Kuo, Ben C. H.; Rodriguez Rubio, Beatriz R.; Chang, Yiu-Yin (Canadian Journal of Counselling and Psychotherapy, 2023)
This study qualitatively examined the evolving experience and change process that occurred when 14 clinical psychology doctoral trainees worked directly with refugee clients as part of their multicultural counselling training. The study collected and analyzed trainees’ post-session critical incident journals based on the Grounded Theory Method. A superordinate theme—Increased Awareness and Responses to Make Cultural Adaptations to Therapy—emerged from the analysis. This superordinate theme, with its eight subthemes, illustrates that the trainees underwent a dynamic developmental progression, involving elements of cultural awareness, knowledge, and skill/action, as they navigated through learning how to respond to and build relationships with refugee clients. The results of the study point to a three-pronged “cognitive-affective-behavioural” working model. This model helps to conceptualize the effects/impacts on trainees’ overall development of multicultural competence and cultural humility through building relationships and offering culturally informed therapy to refugees. Implications for multicultural counselling theory-building, research, and practice are discussed.